Short lasting climatic risks in Romania. Comparative case study: late rimes that took place in May - 1952 and 2011 - Morosanu, Gabriela Adina (MISC, 2013)
The study regarding the late rime on the territory of Romania, by comparing the causes that were at the basis of rime production in May of 1952 and 2011, proves the wide dimension of the hydrometeor, that is characterized by whitish materials bed on the soil surface, and on the objects on the soil, on clear sky, or with weak winds, and relatively high humidity. Due to a repeated series of rimes (like the ones in 1952), this climatic phenomenon can produce a series of damages at most of the crops, through its duration, and especially through its intensity, and by cumulating the effects from one phase to another. The complexity of the synoptic conditions that define late rimes and the effects on agricultural cultures in the first stages (blossom or the formation of the fruits in fruit trees and grapes), as well as the similarity of thermal aberrations and the way of manifestation of arctic air advections, allowed several conclusions to de drown. These regard the territories that are affected the most, the intensity of the phenomenon for each of the two cases, as well as the elaboration of some empirical models for foreseeing the occurrence of late rimes, with the help of nomograph method, with different assurances.